Transcriptomic and Metabolomic Reprogramming from Roots to Haustoria in the Parasitic Plant, Thesium chinense. (20th December 2017) - Ichihashi, Yasunori; Kusano, Miyako; Kobayashi, Makoto; Suetsugu, Kenji; Yoshida, Satoko; Wakatake, Takanori; Kumaishi, Kie; Shibata, Arisa; Saito, Kazuki; Shirasu, Ken
Abstract: Most plants show remarkable developmental plasticity in the generation of diverse types of new organs upon external stimuli, allowing them to adapt to their environment. Haustorial formation in parasitic plants is an example of such developmental reprogramming, but its molecular mechanism is largely unknown. In this study, we performed field-omics using transcriptomics and metabolomics to profile the molecular switch occurring in haustorial formation of the root parasitic plant, Thesium chinense, collected from its natural habitat. RNA-sequencing with de novo assembly revealed that the transcripts of very long chain fatty acid (VLCFA) biosynthesis genes, auxin biosynthesis/signaling-related genes and lateral root developmental genes are highly abundant in the haustoria. Gene co-expression network analysis identified a network module linking VLCFAs and the auxin-responsive lateral root development pathway. GC-TOF-MS analysis consistently revealed a unique metabolome profile with many types of fatty acids in the T. chinense root system, including the accumulation of a 25-carbon long chain saturated fatty acid in the haustoria. Our field-omics data provide evidence supporting the hypothesis that the molecular developmental machinery used for lateral root formation in non-parasitic plants has been co-opted into the developmental reprogramming of haustorial formation in the linage of parasitic plants.